A descriptive epidemiology of netball injuries during competition: a five year study. Issue 4 (December 1995) - Hopper, D; Elliott, B; Lalor, J
Abstract : OBJECTIVE: To investigate the relation between injury profiles - including assessment, treatment, severity, and the perceived reason for the injury - and participation in competitive netball. METHODS: Between 1985 and 1989, approximately 11, 228 netball players participated in a 14 week netball competition held at the major competitive centre in Western Australia; 608 netball players presented to the first aid room with an injury and were assessed and treated by the same physiotherapist and St John First Aid officer. RESULTS: The overall incidence rate during competition was 5.4%, with more injuries occurring in the A grade level of play. Ankle injuries (84%) were most frequent, with 67% of these injuries diagnosed as lateral ligament sprains while a further 10% of players who suffered this classification of injury sustained a fracture to the ankle or foot. Few injuries occurred at the knee joint (8.3%) and only 1.8% of these injuries were diagnosed as an injury to the anterior cruciate ligament. The direct probability of a netball players' risk estimate was 0.054 per person per match which implied that netball was a relatively safe game. Injuries sustained during practice were not included in this study. CONCLUSIONS: Netball is a relatively safe game though the potential for injury increases with the level of competition.